Dichotomy between level broadening and level coupling to electrodes in large area EGaIn molecular junctions - Bâldea, Ioan (The journal of physical chemistry letters, 2024)
Choosing self-assembled monolayers (SAMs) of fluorine-terminated oligophenylenes adsorbed on gold as an illustration, we show that a single-level [molecular orbital (MO)] model can excellently reproduce full I-V curves measured for large area junctions fabricated with a top EGaIn contact. In addition, this model unravels a surprising dichotomy between MO coupling to electrodes and MO broadening. Importantly for the coherence of the microscopic description, the latter is found to correlate with the SAM coverage and molecular and π* orbital tilt angles.
Gesehen am 14.05.2024